Synthesis of indeno-[1,2-b]-quinoline-9,11(6H,10H)-dione and 7,7-dimethyl-10-aryl-7,8-dihydro-5H-indeno[1,2-b]quinoline-9,11(6H,10H )-dione derivatives in presence of heterogeneous Cu/zeolite-Y as a catalyst - Dhengale, Shankar D.; Rode, V. Chandrashekhar; Kolekar, Govind B.; Anbhule, V. Prashant (RSC Advances, 2022)
A simple method for the synthesis of indeno-[1,2-b]-quinoline-9,11-(6H,10H)-dione derivatives and 7,7-dimethyl-10-aryl-7,8-dihydro-5H-indeno[1,2-b]quinoline-9,11(6H,10H )-diones through the reaction of aromatic aldehydes, indan-1,3-dione, dimedone, and p-toluidine/ammonium acetate in the presence of heterogeneous CuO supported on a zeolite-Y catalyst has been investigated in ethanol under reflux conditions. By this method, the reaction time has been reduced, giving an excellent yield of the product. The catalyst was prepared by a hydrothermal method followed by a wet impregnation method. The catalyst had shown Bronsted acid sites and Lewis acid sites. The used catalyst could be actively recycled with a marginal decrease in yield up to five recycles. The prepared catalyst was characterized by FT-IR, pyridine FT-IR, XRD, SEM, EDS, XPS, TEM, and BET surface area analysis. The synthesized compounds were characterized by FT-IR, H-1 NMR, C-13 NMR and GC-MS spectroscopy.